2020
DOI: 10.1186/s13098-020-00574-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA cancer susceptibility candidate 2 (CASC2) alleviates the high glucose-induced injury of CIHP-1 cells via regulating miR-9-5p/PPARγ axis in diabetes nephropathy

Abstract: Background High glucose (HG) induced podocytes injury plays an important role in diabetes nephropathy (DN) development. Long noncoding RNA cancer susceptibility candidate 2 (CASC2) was found to be decreased in serum of DN patients. We aimed to explore the function and possible mechanism of CASC2 in HG induced podocytes injury. Methods Under normal glucose (NG), HG and mannitol stimulated podocyte conditions, the levels of CASC2, microRNA-9-5p (miR-9-5p) and peroxisome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Both corticosteroid and triptolide can protect podocytes by maintaining miR-30s expression and reducing proteinuria (Wu et al 2014;Yang et al 2017). It has been also found that miR-9-5p can alleviate podocyte injury by being regulated by cancer susceptibility candidate 2 (CASC2) and targeting PPARγ (Li et al 2020). Therefore, miR-30s and miR-9-5p can not only be used as biomarkers of podocytes injury but also play a therapeutic role by regulating their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both corticosteroid and triptolide can protect podocytes by maintaining miR-30s expression and reducing proteinuria (Wu et al 2014;Yang et al 2017). It has been also found that miR-9-5p can alleviate podocyte injury by being regulated by cancer susceptibility candidate 2 (CASC2) and targeting PPARγ (Li et al 2020). Therefore, miR-30s and miR-9-5p can not only be used as biomarkers of podocytes injury but also play a therapeutic role by regulating their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolismrelated ceRNA may act as a predictor of the survival outcomes of patients with osteosarcoma (46). CASC2/miR-9-5p/PPARγ alleviates the high glucose-induced cell injury in diabetes nephropathy (47). In polycystic ovary syndrome (PCOS), a ceRNA network is constructed (48), most ceRNA axes are closely related to steroid biosynthesis and metabolic pathways (49), and PWRN2-mediated ceRNA may regulate oocyte nuclear maturation (50).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer susceptibility candidate 2 (CASC2) is located at chromosome 10q26 in humans and was first discovered in 2004 by Baldinu et al [47]. CASC2 acts as a tumor suppressor in various types of cancers [48] and its expression level is reduced in the serum of diabetic nephropathy patients [49], tissues in db/db diabetic mouse, and high glucose-treated human renal mesangial cells [50] and podocyte cells [49][50][51][52]. Upregulation of CASC2 has been shown to attenuate the progression of diabetic nephropathy via various pathways.…”
Section: Casc2mentioning
confidence: 99%